Receptor for advanced glycation end products is protective during murine tuberculosis - Zoelen, Marieke A. D. van; Nawroth, Peter Paul; Bierhaus, Angelika (Molecular immunology, 2012)
The development of active tuberculosis after infection with Mycobacterium tuberculosis is almost invariably associated with a persistent or transient state of relative immunodeficiency. The receptor for advanced glycation end products (RAGE) is a promiscuous receptor that is involved in pulmonary inflammation and infection. To investigate the role of RAGE in tuberculosis, we intranasally infected wild-type (Wt) and RAGE deficient (RAGE−/−) mice with live virulent M. tuberculosis. While lungs of uninfected Wt mice expressed RAGE, in particular on endothelium, M. tuberculosis pneumonia was associated with an enhanced pulmonary expression of RAGE. Lung inflammation was increased in RAGE−/− mice, as indicated by histopathology, percentage of inflamed area, lung weight and cytokine and chemokine levels. In addition, lung lymphocyte and neutrophil numbers were increased in the RAGE−/− mice. RAGE−/− mice had modestly higher mycobacterial loads in the lungs after 3 weeks but not after 6 weeks of infection. Moreover, RAGE−/− mice displayed more body weight loss and enhanced mortality. In summary, pulmonary RAGE expression is increased during tuberculosis. In addition, these data suggest that RAGE plays a beneficial role in the host response to pulmonary tuberculosis.